Social Safeguards and Program Design in PRGT and PSI-Supported Programs. (Policy Papers; Policy Paper ;, 2017)
The Fund provides considerable support to low-income countries (LICs). This includes concessional financing from the Poverty Reduction and Growth Trust (PRGT), which currently carries an interest rate of zero percent. Since 2010, over half of Fund-supported arrangements have involved a PRGT facility. Support for poverty reduction is a core objective of arrangements supported by these facilities. This paper examines how PRGT-supported programs safeguard spending on poor and vulnerable groups within the broader framework of promoting inclusive growth. In some cases, national poverty reduction programs seek to shift expenditures toward social programs in the context of generally higher spending supported by domestic revenue mobilization, grants, or debt financing. In other cases, the goal is to safeguard poor and vulnerable groups from fiscal adjustment and reform measures that could adversely affect them by adopting countervailing policy measures to strengthen social safety nets. In discussing social safeguards, this paper focuses on how and if these objectives are reflected satisfactorily in the design of PRGT and PSI-supported programs. The effectiveness of social spending in improving social outcomes, including by durably reducing poverty, is beyond the scope of the paper.